2014
DOI: 10.1371/journal.pone.0093306
|View full text |Cite
|
Sign up to set email alerts
|

Large Genomic Rearrangements of BRCA1 and BRCA2 among Patients Referred for Genetic Analysis in Galicia (NW Spain): Delimitation and Mechanism of Three Novel BRCA1 Rearrangements

Abstract: In the Iberian Peninsula, which includes mainly Spain and Portugal, large genomic rearrangements (LGRs) of BRCA1 and BRCA2 have respectively been found in up to 2.33% and 8.4% of families with hereditary breast and/or ovarian cancer (HBOC) that lack point mutations and small indels. In Galicia (Northwest Spain), the spectrum and frequency of BRCA1/BRCA2 point mutations differs from the rest of the Iberian populations. However, to date there are no Galician frequency reports of BRCA1/BRCA2 LGRs. Here we used mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 30 publications
(56 reference statements)
2
30
0
Order By: Relevance
“…The drawback of MLPA is that it does not identify LGR breakpoints, which are essential for the recognition of recurrent rearrangements. Other strategies, such as NGS, should be applied to identify the breakpoint (23,24). The relative high frequency of…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The drawback of MLPA is that it does not identify LGR breakpoints, which are essential for the recognition of recurrent rearrangements. Other strategies, such as NGS, should be applied to identify the breakpoint (23,24). The relative high frequency of…”
Section: Discussionmentioning
confidence: 99%
“…Criteria for the inclusion of BART testing at no additional charge as part of the BRACAnalysis are listed in Table 3. Wenstrup et al (23) reported on Myriad's BART clinical assay for LGRs. A total of 1,035 high-risk patients initially underwent a comprehensive BRACAnalysis, which included BRCA1 and BRCA2 full gene sequencing plus five common recurrent BRCA1 LGR mutations.…”
Section: Discussionmentioning
confidence: 99%
“…)del (exon deletion)1–13c. (?_-48)_(4357 + 1_4358-1)del (exon deletion)20c.5213_5277 + 3182delinsT (exon deletion)Fachal L et al 2014 [29]Spain (Galicia)6511-2c. (?_-48)_(80 + 1_81-1)del (exon deletion)1–24c.…”
Section: Introductionmentioning
confidence: 99%
“…LGR (Siyar Ekinci et al, 2015) is a Wnt signal transduction pathway receptor (Fachal et al, 2014) and belongs to the RS5-PO family (Haack et al, 2015). LGR participates in the occurrence and development of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…According to the established protocol (Yan et al, 2015), HCT116 cells were collected for the quantification of the LGR4 protein level (Fachal et al, 2014). Cells were first lysed in buffer for 30 min on ice and were centrifuged to collect proteins.…”
Section: Western Blotmentioning
confidence: 99%